Recent Trends in Synthesis of Chloramphenicol New Derivatives - Anna N. Tevyashova (MDPI AG, 2021)
Chloramphenicol (CAM), the bacteriostatic broad-spectrum antibiotic, isolated from Streptomyces venezuelae during the "golden era" of antibiotic discovery, nowadays has limited clinical potential due to adverse side effects and frequent antimicrobial resistance. Numerous CAM analogs were synthesized in order to find the derivatives with improved pharmacological properties and activity on resistant bacterial strains. This work aims to summarize the most recent achievements in obtaining new CAM analogs reported during the last five years. Current investigations are mainly focused on elucidating the molecular basis of the mode of CAM action and determining the mechanisms of resistance to this class of antibiotics or on studies of the possible use of the CAM scaffold to search for therapeutic agents with different CAM modes of action-such as selective antiproliferative agents or bacterial cell wall biosynthesis inhibitors. Hopefully, a deeper understanding of the CAM interactions with the target and its specificity will generate research ideas for developing new effective drugs.